Leadership and Growth : Commission on Growth and Development - Brady, David; Spence, Michael (World Bank, 2012)
In May 2008, the commission on growth and development (the growth commission) issued its report entitled 'the growth report'. In it the commission attempted to distill what had been learned in the past two decades, from experience and academic and policy research, about strategies and policies that produced sustained high growth in developing countries. It became clear in the course of the work that politics, leadership, and political economy (the interaction of economic and political forces and choices) were centrally important ingredients in the story. Dealing with the politics and the interaction of political and economic forces is a work in progress in research, an important one. Given this breadth, one of the editors' roles is to focus the reader's attention on what they take to be common issues across these chapters. These common problems are fourfold: (1) promoting national unity; (2) building good, solid institutions; (3) choosing innovative and localized policies; and (4) creating political consensus for long-run policy implementation. This report represent an excellent first step toward understanding the role of leadership in generating economic growth, and the author hope that they generate ideas and lead to new research on the problem of leadership in economic growth.